Manaqib In The Reception of The Banjar Community: Sanctification of Religious Text - Jannah, Miftahul (IAIN Surakarta, 2018)
Manaqib is a familiar term at moslem society in Indonesia, especially at Nahdiyyin circle, and also for Banjarese moslem society (an ethnic in South Kalimantan, Borneo). Moreover, this manaqib is already become a tradition since several decades ago, but its still flare up and lively until now. Consistency of this manaqib tradition is not release from the influence of the charismatic scholars which always spread the call to continue to traditionalize the reading of manaqib, one of which is through their works in the field of this manaqib. Among them is where the classical ulama like Siti Khadijah al-Kubra, Shaikh Samman al-Madani, Shaikh Abdul Qadir al-Jailani and the local ulama are like the Shaikh Arsyad al-Banjari, Tuan Guru Kasyful Anwar, Tuan Guru M. Zaini Gani, and many others. With qualitative-anthropological studies, this study concludes that the writing of the books by the Banjar clerics was influenced by the strength of the tarekat teachings, especially the Naqsabandiyah and Sammaniyah orders. The influence is the emergence of public trust in the sacredness of the reading of the manaqib text itself, which is believed to bring various blessings such as avoiding calamity, expanding fortune, and being aware of various other purposes. Keywords : text knowledge, manaqib, reception, Banjarese tradition